Energy Efficient Synthesis of Ordered Mesoporous Carbon Nitrides with a High Nitrogen Content and Enhanced CO2 Capture Capacity. Issue 45 (24th July 2017) - Park, Dae‐Hwan; Lakhi, Kripal S.; Ramadass, Kavitha; Kim, Min‐Kyu; Talapaneni, Siddulu N.; Joseph, Stalin; Ravon, Ugo; Al‐Bahily, Khalid; Vinu, Ajayan
Abstract: Highly ordered mesoporous carbon nitrides (MCN) with 3D structure and a high nitrogen content are successfully prepared for the first time using "uncalcined" mesoporous silica template, KIT‐6 and 3‐amino‐1, 2, 4‐triazole as a single molecular carbon and nitrogen precursor. The prepared MCN with C and N stoichiometry of C3 N5 shows unique CN framework and exhibits the CO2 capture capacity of 5.63 mmol g −1 at 273 K and 30 bar, which is higher than that of MCN with 2D structure and C3 N4 stoichiometry. Abstract : Catch and don′t release : Mesoporous carbon nitrides (MCN) with highly ordered 3D structure and a high nitrogen content show a unique CN framework with C and N stoichiometry of C3 N5 and the CO2 capture capacity up to 5.63 mmol g −1 at 273 K and 30 bar.